Mechanical complications after myocardial infarction in a National Reference Hospital - Espinoza Alva, Daniel (2022)
Objective. To determine the clinical characteristics, therapeutic and in-hospital mortality of patients with mechanical complications post myocardial infarction. Materials and methods. Observational, descriptive and retrospective study. We included patients >18 years old with a diagnosis of mechanical complication post myocardial infarction hospitalized at the Instituto Nacional Cardiovascular- INCOR in Lima -Peru, from January 1, 2017 to December 31, 2021. Variables like clinical characteristics, treatments, complications, and in-hospital mortality were studied. Results. We found 37 cases, with a predominance of males (73.0%) and a median age of 73 years old. The location of the myocardial infarction was 51.4% in the anterior wall and 43.2% in the inferior wall. The patients received reperfusion therapy with fibrinolysis in 5 cases (13.5%), coronary angioplasty in 5 (13.5%), and 73% received only medical management prior to the diagnosis of mechanical complications. Of the 37 patients, 13 (35.1%) presented isolated ventricular free wall rupture, 12 (32.4%) isolated interventricular septum rupture, 10 (27.0%) the combination of ventricular free wall rupture and interventricular septum, and 2 (5.4%) papillary muscle rupture. In-hospital mortality was 51.4%. Conclusions. The ventricular free wall rupture was the most frequent complication, patients with mechanical complications after myocardial infarction still maintain high intra-hospital mortality rates, mainly in those who did not have adequate surgical treatment.